First occurrence of Limnoperna fortunei (Dunker, 1857) in the Rio Tietê watershed (São Paulo State, Brazil) - DC. Pareschi; T. Matsumura-Tundisi; GR. Medeiros; AP. Luzia; JG. Tundisi (Brazilian Journal of Biology)
This paper describes the recent expansion of the geographical distribution of Limnoperna fortunei (Dunker, 1857) in the Tietê River watershed, São Paulo State, Brazil. Estimations related to the velocity of invasion and its causes are presented. Ecological implications related to biodiversity and possible changes in the food chain are discussed.